Nailfold microvascular abnormalities are associated with a higher prevalence of pulmonary arterial hypertension in patients with MCTD. (14th March 2022) - Todoroki, Yasuyuki; Kubo, Satoshi; Nakano, Kazuhisa; Miyazaki, Yusuke; Ueno, Masanobu; Satoh-Kanda, Yurie; Kanda, Ryuichiro; Miyagawa, Ippei; Hanami, Kentaro; Nakatsuka, Keisuke; Saito, Kazuyoshi; Nakayamada, Shingo; et al.
Abstract: Objective: MCTD manifests with microvasculopathy and overlapping clinical features of SLE, SSc and idiopathic inflammatory myopathies (IIM). The aim of this study was to investigate the clinical significance of microvasculopathy in patients with MCTD using nailfold videocapillaroscopy (NVC). Methods: Fifty patients with newly diagnosed and untreated MCTD were enrolled in this multicentre, prospective and observational study. Clinical features and NVC findings were assessed at baseline and after 1 year post-intervention, along with disease controls [SLE ( n  = 40), SSc ( n  = 70) and IIM ( n  = 50)]. Results: All MCTD patients presented Raynaud's phenomenon and were positive for anti-U1 RNP antibodies, and 22.0% (11/50) had pulmonary arterial hypertension (PAH). The prevalence of NVC scleroderma patterns in MCTD was 38.0%, which was lower than SSc (88.6%) but higher than SLE (10.0%). In addition, when we divided MCTD patients into two groups by presence or absence of NVC scleroderma patterns, we found a higher prevalence of PAH in patients with NVC scleroderma patterns. Namely, NVC scleroderma patterns were observed in all MCTD patients with PAH, and in 21.0% of those without PAH. After intensive immunosuppressive therapy, NVC scleroderma patterns disappeared in half of the MCTD patients but were not changed in SSc patients. Conclusions: MCTD differed from SLE, SSc and IIM in terms of the prevalence and responsiveness of NVC scleroderma patterns to immunosuppressive therapy. Detection of nailfold microvascular abnormalities in MCTD could contribute to predicting PAH and help us to understand further aspects of the pathogenesis of MCTD.